Layer-by-layer assembled conductive films based on poly(3,4-ethylenedioxythiophene) and polypyrrole composites for hybrid supercapacitors - Kulandaivalu, Shalini (2019)
Electrochemical supercapacitors are highly potential and environment-friendly storage system that widely used in electronic devices considered as a good solution to reduce the global environmental issues. A good electrochemical supercapacitor should possess remarkable specific energy, long shelf life, fast charge-discharge capacity and good specific power which can be improved by designing the electrode materials. In this study, the layer-by-layer (LBL) approach has been shown to be a viable option in the fabrication of electrode materials for supercapacitors. Two different preparation methods, electrodeposition (chronoamperometry) and vacuum filtration have been chosen to design the electrode materials. The focus was placed on multi-layered composition as electrode materials for a symmetrical supercapacitor device, where each layer was made of composites containing two or more materials. By carefully controlling the number of layers and the order of the layers, high-performance LBL assembled composite films have been obtained. X-ray diffractometry, Raman spectroscopy, Fourier transform infrared spectroscopy, field emission scanning electron microscopy, Brunauer–Emmett–Teller analysis and X-ray photoelectron spectroscopy have been used to characterize the as-formed layered composites. In this work, different composition of materials consisting of conducting polymers, i.e. poly(3,4-ethylenedioxythiophene) (PEDOT) and polypyrrole (PPy), carbon-based materials, i.e. graphene oxide (GO), reduced graphene oxide (rGO), nanocrystalline cellulose (NCC) and multi-walled carbon nanotubes (MWCNTs) and nickel-cobalt layered double hydroxides (Ni-Co LDHs) were incorporated to form multilayered composites. The electrochemically deposited PEDOT/GO with PEDOT/NCC bilayer composite showed good performance with high specific capacitance (129.03 F g-1 at 25 mV s-1), good capacity retention (85% of initial value after 2000 cycles), remarkably low charge transfer resistance (4.02 Ω) and good specific power and specific energy compared to its individual binary hybrid nanocomposites. After replacing the PEDOT with PPy to form composite film via vacuum filtration method, the as-formed bilayer composite film showed good improvement in the supercapacitive performances. This bilayer film had a surface area of 42.88 m2 g-1, a mesoporosity system, and delivered a high specific capacitance of 562.9 F g-1 at 3 mV s-1 with a maximum specific energy of 19.3 Wh kg-1 and maximum specific power of 884.6 W kg-1. Subsequently, by substituting the second layer with MWCNTs/rGO/NCC, the film with mesopores (0.558 cm3 g-1) and specific surface area of 106.02 m2 g-1 exhibits a high specific capacitance of 882.2 F g-1 at 10 mV s-1, remarkable cycling stability of ~90% over 10000 cycles and a high specific energy of 44.6 Wh kg-1 with a high specific power of 2889.9 W kg-1. Another separate study has been carried out by layering Ni-Co LDHs hexagonal flakes on PPy/rGO to investigate the electrochemical performances of this electrode material. The as-obtained composite film endowed Ni2+ and combination of Co2+/Co3+ valence states. Interestingly, outstanding specific capacitance of 1018 F g-1 at 10 mV s-1 and specific energy of 46.5 Wh kg-1 at 464.9 W kg-1 were obtained in a symmetrical device. The works carried out in this study have shown that the LBL approach is an inspiring and promising way to produce high-performance electrode materials for supercapacitors. Moreover, the presence of composite in each layer via this approach has increased the surface area of the material and synergy contribution of each material for the overall performances.